TGF-β in Mice Ameliorates Experimental Autoimmune Encephalomyelitis in Regulating NK Cell Activity - J. Xu; Y. Wang; H. Jiang; M. Sun; J. Gao; A. Xie (Cell Transplantation, 2019)
Multiple sclerosis is a disease characterized by inflammation and demyelination located in the central nervous system. Experimental autoimmune encephalomyelitis (EAE) is the most common animal model for multiple sclerosis (MS). Although the roles of T cells in MS/EAE have been well investigated, little is known about the functions of other immune cells in the neuroinflammation model. Here we found that an essential cytokine transforming growth factor β (TGF-β) which could mediate the differentiation of Th17/regulatory T cells was implicated in the natural killer (NK) cells’ activity in EAE. In EAE mice, TGF-β expression was first increased at the onset and then decreased at the peak, but the expressions of TGF-β receptors and downstream molecules were not affected in EAE. When we immunized the mice with MOG antigen, it was revealed that TGF-β treatment reduced susceptibility to EAE with a lower clinical score than the control mice without TGF-β. Consistently, inflammatory cytokine production was reduced in the TGF-β treated group, especially with downregulated pathogenic interleukin-17 in the central nervous system tissue. Furthermore, TGF-β could increase the transcription level of NK cell marker NCR1 both in the spleen and in the CNS without changing other T cell markers. Meanwhile TGF-β promoted the proliferation of NK cell proliferation. Taken together, our data demonstrated that TGF-β could confer protection against EAE model in mice through NK cells, which would be useful for the clinical therapy of MS.